Cartografia de um ambiente escolar com discentes do IFPE em uma abordagem sociodramática. - Santos, Cláudia da Silva (2017)
This work sought to chart the way teaching practices are perceived from the look of a group of students from the Federal Institute of Pernambuco – IFPE. It was intended, through an interventional approach and using Sociodrama, to stimulate participants to dramatize their relationships and experiences at the school environment. Adolescent students attending Electronic course at secondary school level in Campus Recife (IFPE) participated the field research. Most of these students live in the outskirts of the city and have poor socioeconomic conditions. The work was developed in groups and the choice of the interventional sociodramatic mode seemed pertinent to the extent that would make the (re) signification of the relationship student-student, student-teacher, teacher-teacher. It is believed that the understanding of this experience, as well as the comprehension of the institutional and personal conflicts and the motivation to create spaces of dialogue consist on a powerful way to meaningful learning within the academic community. The cartographic method was the ground on which the sociodramatic process took place, allowing to trace the students’ subjective settings concerning their learning processes, as well as the place of the teacher and of the institution in their daily school life. Sociodramatic sessions unfolded a needy and worrying school reality. During the meetings, It was realized how the decision to opt for a technical course was influenced by the family. However, during the drama performances, it became notorious that these families do not take care of the students throughout the course. They feel the pressure of the family and the teachers’ demands. On the other hand, most teachers come from the “hard” areas of Science and do not have a licentiate degree in teaching, which is seen as a problem by the students. For them, the absence of didactics undermines the teachinglearning process. Most of the teachers are presented as incomprehensible, rigorous and extremely demanding in terms of marks. These elements lead us to propose a thorough review, less focused on syllabus and more careful with intrasubjective and affective aspects. As well as the supply of spaces, including sociodramatic sessions, for students and teachers to talk and (re) think about their daily school life.